Numerical simulation of reservoir sediment and effects on hydro-dynamic response of arch dams. - Chuhan, Zhang (Earthquake engineering & structural dynamics.)
Based on the dynamic theory for saturated porous media by Biot (Journal of the Acoustical Society of America), a numerical model is presented to analyse the reflection behaviours of reservoir sediment and compared with those from the visco-elastic model. It is concluded that the two models give very similar results of reflection coefficient x within the frequency range of interest. Then, using the two models. the change of the reflection coefficients x with various sedimentation parameters and excitation frequencies are studied in detail. The results are further used in the analysis of response functions of hydro dynamic pressures on, and structural displacements of the Xiang Hond Dian arch dam, for which some results from a field vibration test are available. It appears that effects of water compressibility with sediment reflection on hydro dynamic pressures and structural response are not significant for this specific case.